Short-term tidal level prediction using normal time-frequency transform. (15th May 2018) - Cai, Song; Liu, Lintao; Wang, Guocheng
Abstract: This study introduces a new method named "Inaction method" (also referred to as a "line-pass" filter, in the filtering language) for predicting short-term tidal levels. The "Inaction method", which is based on normal time-frequency transform (NTFT) theory, can recognize and extract harmonic/quasi harmonic components of a tidal signal without an inverse transform. Conventional methods decompose tidal levels into a series of harmonic constituents, and each constituent has its own fixed amplitude and frequency. Instead of those harmonic parameters, the "Inaction method" enables the user to directly and exactly recover the harmonic with instantaneous amplitude, frequency and phase. Apply this method more than once can reduce edge effect and retrieve instantaneous harmonic information. Based on instantaneous harmonic information, extracted tidal constituents then can be used to predict future tidal levels. Unlike harmonic analysis, which always requires a long period of tidal level record to make sure an accurate prediction, "Inaction method" can use short-term data. In addition, the conventional method require a tide table to determine frequencies while the proposed method does not. Tide gauge measurements from Quarry bay, Hong Kong are tested in this study. Results demonstrate the capacity of the "Inaction method" to generate short-term tidal level forecast based on correlation coefficient (0.92–0.99), root mean square error (about 4%–8% of the tidal range). Highlights: Instantaneous amplitude, instantaneous frequency and instantaneous phase of a harmonic component of signal can be obtained by "Inaction method" presented in this study, which can not be solved by conventional method such as Fourier transform, Gabor transform, Continuous Wavelet transform and S transform. To obatain instantaneous information at the end of observation which is important for short-term prediction, we used "Inaction method" repeatedly with different window width to reduce edge effect. We made a comparison between "Inaction method" and classical harmonic analysis on tidal level prediction.Results confirmed the applicability of the tested method for predicting short-term tidal levels using only a short data series.